Male Readiness for Contraception and its Determinants: A Cross-Sectional Study - Iqbal, Sana; Azam, Naila; Maroof, Saira; Irshad, Shamim; Rashid, Sadaf; Sultan, Nadia (Pakistan Armed Forces Medical Journal, 2024)
Objective: To identify the socio-economic determinants for male readiness for contraception and predictors of contraceptive prevalence among the male population.Study Design: Cross-sectional study.Place and Duration of Study: Family Planning Clinic at a Tertiary Care hospital, Rawalpindi Pakistan, from Jun 2020 to Feb 2021.Methodology: A total of 328 participants, recruited through purposive sampling and assessed through a semi-structured validated questionnaire regarding male readiness for contraception. Mean and SD was calculated for the quantitative variable while frequency distribution for the qualitative variables. Chi-square test was used to measure association, and regression analysis was done to analyze the most significant predictor of male contraceptive behavior.Results: A total of 328 male participants were included in the study, out of which 177(53.9%) had never used any family planning method whereas 155(43.9%) had used contraception at some point in their life. Knowledge about female contraceptives, social network participation regarding family planning methods, and knowledge about male contraceptives methods were statistically significant predictors of male contraceptive practices (p